DEVELOPMENT OF ZISWAF LABORATORY MODEL INTEGRATED MB-KM CURRICULUM USING ROWNTREE MODEL - Afrianty, Noni; Setiawan, Adi (An-Nisbah: Jurnal Ekonomi Syariah, 2023)
Abstrak: Penelitian ini bertujuan untuk melakukan pengembangan model laboratorium yang teirntegrasi dengan kurikulum MB-KM dengan menggunakan pendekatan Model Rowntree. Hasil penelitian ini menunjukkan bahwa pedoman yang dikembangkan sebagai petunjuk pelaksanaan PPL dan KKN MB-KM dikategorikan baik, sehingga dapat digunakan dalam pengembangan model laboratorium ZISWAF Fakultas EKonomi dan Bisnis Islam UIN Fatmawati Sukarno Bengkulu Kata kunci: Model Laboratorium, Kurikulum MB-KM, Model Rowntree Abstract: This study aims to develop a laboratory model that integrates with the MB-KM curriculum using the Rowntree Model approach. The results of this study show that the guidelines developed as guidelines for the implementation of PPL and KKN MB-KM are categorized as good, so that they can be used in the development of the ZISWAF laboratory model of the Faculty of Islamic Economy and Business UIN Fatmawati Sukarno Bengkulu Keywords: Laboratory Model, MB-KM Curriculum, Rowntree Model